Child sexual abuse material in child-centred institutions: situational crime prevention approaches. Issue 1 (2nd January 2020) - Krone, Tony; Spiranovic, Caroline; Prichard, Jeremy; Watters, Paul; Wortley, Richard; Gelb, Karen; Hunn, Charlotte
ABSTRACT: This paper focuses on the potential for child-centred institutions to use situational crime prevention (SCP) strategies to prevent or reduce child sexual abuse material (CSAM) offending as a distinct form of child sexual abuse (CSA). We discuss the failure of the Royal Commission into Institutional Responses to Child Sexual Abuse in Australia to address the potential for CSAM offending to occur in child-centred institutions. Our premise is that CSAM offending is markedly shaped by the situation in which it occurs, rather than by any pre-existing preparedness to offend sexually against children. In this context, SCP for CSAM offending must be considered as part of overall strategies to combat CSA in institutional settings. However, we acknowledge that effective implementation of SCP in this area is not straightforward. We consider some of the challenges in implementing SCP at an institutional level.